Inflation Persistence and the Limited Impact of Monetary Policy Instruments Evidence from Indonesia - Wila Delvia; Surya Dewi Rustariyuni (Journal of Citizenship, 2026)
Inflation is one of the key indicators in maintaining a country’s economic stability. Changes in global economic conditions, the COVID-19 pandemic, and the dynamics of monetary policy have caused inflation in Indonesia to fluctuate during the 2015–2025 period. Monetary policies implemented by Bank Indonesia through the control of interest rates, money supply, and exchange rate stability play an important role in maintaining price stability. In addition, inflation in previous periods is also presumed to influence current inflation through the phenomenon of inflation persistence. This study aims to analyze the effects of interest rates, changes in money supply, exchange rate changes, and inflation lag on inflation in Indonesia during the 2015–2025 period. This study employed a quantitative approach using quarterly time-series data from 2015 to 2025. The data used were secondary data obtained from Bank Indonesia and Statistics Indonesia. The analytical techniques employed included descriptive statistical analysis, multiple linear regression analysis, classical assumption tests, simultaneous significance testing (F-test), and partial significance testing (t-test) using the EViews program. The results indicate that, simultaneously, interest rates, changes in money supply, exchange rate changes, and inflation lag have a significant effect on inflation in Indonesia. Partially, interest rates have a negative and insignificant effect on inflation, changes in money supply have a positive and insignificant effect on inflation, exchange rate changes have a positive and insignificant effect on inflation, while inflation lag has a positive and significant effect on inflation in Indonesia. These findings indicate that inflation in Indonesia tends to be influenced by inflation persistence from previous periods. The implications of this study suggest that inflation control does not solely depend on current monetary policy but also needs to consider the influence of inflation in previous periods. Therefore, Bank Indonesia needs to maintain the consistency of its monetary policy through the control of interest rates, liquidity, and exchange rate stability in order to preserve price stability and support national economic stability. Keywords: monetary policy, interest rates, money supply, exchange rate, inflation lag, inflation